Novel Insights into the Ontogenetic and Functional Heterogeneity of Macrophages in Synovial Tissue and Bone - Percin, Gulce Itir; Grüneboom, Anika; Waskow, Claudia; Culemann, Stephan (Osteologie, 2021)
Inflammatory joint diseases like rheumatoid arthritis (RA) belong to the most prevalent autoimmune disorders. RA is characterized by a massive infiltration of immune cells into synovial tissue, cartilage destruction and bone erosion. The perpetuating inflammatory and destructive milieu is associated with severe pain and culminates in complete disability of synovial joints. The events initiating RA are still not fully understood and the treatments are mainly confined to strategies that modify and inhibit the body’s immune system. Macrophages and osteoclasts (OC) are myeloid cells of the innate immune system and are considered to play a central role in the inflammatory and destructive events of arthritis by production of inflammatory cytokines and mediating pathological bone resorption. In recent years, the use of novel fate mapping strategies identifying the origin and cellular development (ontogeny) of OC and macrophages in conjunction with new genetically modified mouse models, single cell analysis and advanced imaging techniques substantially changed our understanding on the ontogenetic and functional heterogeneity of these cells.